Effectiveness of Cold Compress Therapy to Reduce the Intensity of Perineal Laceration Pain in Post-Partum Women - Surita Br Ginting; Yufdel; Elny Lorensi Silalahi (Postgraduate, University of Mataram, 2023)
Perineal lacerations in postpartum Mothers cause pain which can affect mobility and can cause complications such as infection, postpartum bleeding, and psychological impacts. This research aims to determine the effectiveness of cold compress therapy in reducing the intensity of perineal laceration pain in postpartum mothers. This research method is pre-experimental with a one-group pre-post Test design. The sample for this research was 37 postpartum mothers. Sampling used purposive sampling. Data were collected using the NRS (Numeric Rating Scale) and analyzed using the Wilcoxon test. The results of the research after being given cold compress therapy for 15 minutes showed a p-value of 0.00<0.05, which means that there was the effectiveness of cold compress therapy in reducing the intensity of perineal laceration pain in Postpartum mothers at the Niar Maternity Clinic, Deli Serdang Regency. This study concludes that cold compress therapy is effective in reducing perineal laceration pain in post-partum mothers. It is hoped that the Niar Clinic can apply cold compress therapy as a complementary therapy at the Maternity Clinic to reduce perineal laceration pain in post-partum mothers